First report of serotype 23B Streptococcus pneumoniae isolated from an adult patient with invasive infection in Japan. (May 2017) - Takamatsu, A.; Kawaguchiya, M.; Chang, B.; Ito, M.; Hirano, Y.; Katsuta, S.; Matsuzaka, S.; Serizawa, Y.; Kobayashi, N.
Abstract: Serotype 23B Streptococcus pneumoniae was isolated from a 67-year-old Japanese patient with meningitis. This isolate was susceptible to penicillin G, while genotyped as gPISP with a mutation in a penicillin-binding motif in PBP2b. The 23B isolate was assigned to ST11996 that is related to CC439, a dominant group among serotype 23B.